Enhancing Early Childhood Creativity Through Augmented Reality-Assisted Drawing Pattern Development at Nurul Qolbi Kindergarten - Indrayani, Komala; Meliani, Fitri Meliani; Fuji Aryani, Dwi; Suniah, Suniah; Purnamasari, Devi; Intan, Soleha (Hadlonah: Jurnal Pendidikan dan Pengasuhan Anak, 2025)
Developing creativity in early childhood is very important because early childhood is a golden period in the growth and development of children. However, the results of observations at Nurul Qolbi Kindergarten show that children's creativity is still less than optimal due to monotonous learning and minimal use of innovative learning media. This study aims to improve the creativity of early childhood through the development of drawing patterns with the help of Augmented Reality (AR) technology at Nurul Qolbi Kindergarten. This Classroom Action Research was conducted on children aged 4-5 years for two cycles with the Kurt Lewin model. Data were collected using observation, documentation and assessment techniques of children's work. Data analysis was carried out by data reduction, data presentation and drawing conclusions. The results of the study showed that before the application of AR, children's creativity was relatively low. However, after the application of AR-assisted drawing pattern development learning, there was an increase in children's creativity, both in original ability, fluency, flexibility, and elaboration of ideas. It was concluded that the use of Augmented Reality (AR)-assisted drawing pattern development can improve the creativity of early childhood. It is recommended that educators can utilize this technology-based learning media to create a more innovative and interactive learning experience.